2017
DOI: 10.1038/s41467-017-00896-8
|View full text |Cite
|
Sign up to set email alerts
|

Biogenic manganese oxide nanoparticle formation by a multimeric multicopper oxidase Mnx

Abstract: Bacteria that produce Mn oxides are extraordinarily skilled engineers of nanomaterials that contribute significantly to global biogeochemical cycles. Their enzyme-based reaction mechanisms may be genetically tailored for environmental remediation applications or bioenergy production. However, significant challenges exist for structural characterization of the enzymes responsible for biomineralization. The active Mn oxidase in Bacillus sp. PL-12, Mnx, is a complex composed of a multicopper oxidase (MCO), MnxG, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
77
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 78 publications
(89 citation statements)
references
References 66 publications
(73 reference statements)
2
77
0
Order By: Relevance
“…It is then desirable to develop facile, cheap, environmentally benign, and size control routes to prepare MnO2 nanoparticles [34]. In particular, biogenic approaches for the preparation of nanomaterials can be a good alternative to achieve the advantages mentioned above [35]. Non-hazardous chemicals, biodegradable polymers, available fruits, vegetables, herbs containing high concentration of polyphenols can act as antioxidants or reducing agents and can also provide a protective coating.…”
Section: Introductionmentioning
confidence: 99%
“…It is then desirable to develop facile, cheap, environmentally benign, and size control routes to prepare MnO2 nanoparticles [34]. In particular, biogenic approaches for the preparation of nanomaterials can be a good alternative to achieve the advantages mentioned above [35]. Non-hazardous chemicals, biodegradable polymers, available fruits, vegetables, herbs containing high concentration of polyphenols can act as antioxidants or reducing agents and can also provide a protective coating.…”
Section: Introductionmentioning
confidence: 99%
“…We have previously shown that SID produces fragments in which the charge is more symmetrically partitioned than it is in CID and that products can remain compact (13)(14)(15). In addition, we have demonstrated that SID disassembly pathways are consistent with the known protein assembly pathways and hence can provide structural information on known and unknown structures (16)(17)(18). To expand upon…”
mentioning
confidence: 99%
“…In this technique, protein complexes are dissociated by collision with a surface. The SID products of a complex are often sufficient to gain insight into the complex architecture (26,27). SID was performed by directing and accelerating the protein complex ions to an off-axis surface.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, ion mobility (IM) measurements can be used to also determine their collision cross-sections (CCSs) in a combined IM-MS approach. These IM-MS measurements provide information on the stoichiometry and shape of the intact protein complex in the gas phase (24)(25)(26)(27). The protein complex ion of a particular charge state can be selected by a quadrupole and subjected to surface-induced dissociation (SID) before IM-MS. SID is a single-step, high-energy activation method, wherein noncovalent dissociation of the complex leads to generation of Significance Recent advancements in computational protein design have enabled the generation of proteins and protein complexes that are not present in nature.…”
mentioning
confidence: 99%
See 1 more Smart Citation